The Natural History of Untreated Primary Hypogammaglobulinemia in Adults: Implications for the Diagnosis and Treatment of Common Variable Immunodeficiency Disorders (CVID) - Ameratunga, Rohan; Ahn, Yeri; Steele, Richard; Woon, See-Tarn (Frontiers in Immunology, 2019)
Background: Adults with primary hypogammaglobulinemia are frequently encountered by clinicians. Where IgG levels are markedly decreased, most patients are treated with subcutaneous or intravenous immunoglobulin (SCIG/IVIG), because of the presumed risk of severe infections. The natural history of untreated severe asymptomatic hypogammaglobulinemia is thus unknown. Similarly, there are no long-term prospective studies examining the natural history of patients with moderate reductions in IgG. Methods: In 2006, we began a prospective cohort study of patients with symptomatic and asymptomatic reductions in IgG who were not immediately commenced on SCIG/IVIG. Over the course of 12 years, 120 patients were enrolled in the NZ hypogammaglobulinemia study (NZHS) including 59 who were asymptomatic. Results: Five patients with profound primary hypogammaglobulinemia (IgG < 3 g/l), who were not on regular SCIG/IVIG have remained well for a mean duration of 139 months. This study has also shown most asymptomatic patients with moderate hypogammaglobulinemia (IgG 3.0–6.9 g/l) have been in good health for a mean observation period of 96 months. We have only identified one asymptomatic patient with moderate hypogammaglobulinemia who experienced progressive decline in IgG levels to <3 g/l and was accepted for IVIG replacement. Prospective monitoring has shown that none have suffered catastrophic infections or any of the severe autoimmune or inflammatory sequelae associated with Common Variable Immunodeficiency Disorders (CVID). Unexpectedly, 18.1% of asymptomatic and 41.6% of symptomatic hypogammaglobulinemic patients spontaneously increased their IgG into the normal range (≥7.0 g/l) on at least one occasion, which we have termed transient hypogammaglobulinemia of adulthood (THA). In this study, vaccine challenge responses have correlated poorly with symptomatic state and long-term prognosis including subsequent SCIG/IVIG treatment. Conclusions: In spite of our favorable experience, we recommend patients with severe asymptomatic hypogammaglobulinemia are treated with SCIG/IVIG because of the potential risk of severe infections. Patients with moderate asymptomatic hypogammaglobulinemia have a good prognosis. Patients with symptomatic hypogammaglobulinemia are a heterogeneous group where some progress to SCIG/IVIG replacement, while many others spontaneously recover. This study has implications for the diagnosis and treatment of CVID.